Teachers in Malaysia - Are they evolving or dissolving? - Mansor, Azlin Norhaini; Fisher, Lorna; Rasul, Mohamad Sattar; Ibrahim, Mohd Burhan; Yusoff, Nurhayati (2012)
Malaysia has seen many changes to the education system over the last fifty years and the rapidity and frequency of those changes in the last twelve years have lead parents, employers and even the teachers themselves to ask where are we going, what is being taught, how is it being taught and most importantly who are the people that now teach. Do they have the qualities of character, passion, and motivation? If the future of a nation rests on the professional educator are we attracting the best role models, mentors and skill imparters? This qualitative research proposal seeks to explore whether the quality of Teachers in Malaysia is improving and evolving or is the quality of the Teacher and the teaching profession going downhill. The findings are based on the perception of three parent cum professional educators from different economic background, gender, race and working environment. The study found that what matters most - the passion and pride in the teaching profession, is really dissolving, albeit slowly yet surely. MOE’s emphasis on qualifications, higher salary and better career path does not seem to translate into quality educators, more like working around the edges of the issue rather than finding the answer. Thus, the findings within the limitations of this study strongly suggest that recent efforts to enhance the quality of teachers are failing implicating that further study and investigation into the ‘soft’ skills required in the education of the educator is greatly needed.